2024
DOI: 10.5194/acp-24-1429-2024
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the vertical structure of the atmospheric boundary layer in the central Arctic during MOSAiC

Gina C. Jozef,
John J. Cassano,
Sandro Dahlke
et al.

Abstract: Abstract. Observations collected during the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) provide an annual cycle of the vertical thermodynamic and kinematic structure of the atmospheric boundary layer (ABL) in the central Arctic. A self-organizing map (SOM) analysis conducted using radiosonde observations shows a range in the Arctic ABL vertical structure from very shallow and stable, with a strong surface-based virtual potential temperature (θv) inversion, to deep and near n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 96 publications
0
0
0
Order By: Relevance
“…These six near-surface stability regimes range from near neutral conditions (NN; dθ/dz < 0.5 K (100 m) −1 ) to extremely strongly stable conditions (ESS; dθ/dz > 30 K (100 m) −1 ). Thresholds to distinguish between these six regimes -near neutral (NN), weak stability (WS), moderate stability (MS), strong stability (SS), very strong stability (VSS), and extremely strong stability (ESS) -were defined by Dice et al (2023) and Jozef et al (2024) (Table 2) and were found to have robust applications in both the Antarctic and Arctic. Stability regimes aloft, just above the boundary layer, were also defined, as many of the radiosonde profiles have enhanced stability above layers of weaker, near-surface stability.…”
Section: Definition Scheme For Boundary Layer Stability Regimesmentioning
confidence: 99%
“…These six near-surface stability regimes range from near neutral conditions (NN; dθ/dz < 0.5 K (100 m) −1 ) to extremely strongly stable conditions (ESS; dθ/dz > 30 K (100 m) −1 ). Thresholds to distinguish between these six regimes -near neutral (NN), weak stability (WS), moderate stability (MS), strong stability (SS), very strong stability (VSS), and extremely strong stability (ESS) -were defined by Dice et al (2023) and Jozef et al (2024) (Table 2) and were found to have robust applications in both the Antarctic and Arctic. Stability regimes aloft, just above the boundary layer, were also defined, as many of the radiosonde profiles have enhanced stability above layers of weaker, near-surface stability.…”
Section: Definition Scheme For Boundary Layer Stability Regimesmentioning
confidence: 99%